Study on Influence of Water-Cement Ratio on The Strength of Micro Steel Fiber Reinforced Concrete (MSFRC) - Yunas, Muhamad Fareez; Mohd Zuki, Ts. Dr. Sharifah Salwa (Recent Trends in Civil Engineering and Built Environment, 2022)
Steel fiber reinforced concrete (SFRC) is the most commonly used Fiber FRC in construction industry. SFRC is favored because it can prevent early cracks in concrete. The objectives of this study are to investigate the influence of water cement ratio towards the strength of micro steel fiber reinforced concrete (MSFRC). This study focuses on the strength of MSFRC under different water-cement (w/c) ratio. In this study, a constant 1.0% of fiber volume percentage with 12mm length of copper coated micro steel fiber was added into the mix concrete with different water cement (w/c) ratio. The variation of w/c ratio used in this study are 0.3, 0.4, 0.5 and 0.6. At hardened state, the compressive strength test was conducted at 7th and 28th days of curing and for splitting tensile strength was conducted on the 28th day of curing to show the mechanical properties of concrete tested and slump test is conducted to assess the consistency of concrete at fresh state. The study shows that, the optimum water-cement (w/c) ratio of MSFRC designed grade 30 is 0.4 which is lesser than normal grade 30 concrete.